Citizen-centric capacity development for ICT4D: the case of continuing medical education on a stick. Issue 3 (2nd July 2020) - Li, Yan; Thomas, Manoj A.; Stoner, Debra; Rana, Sarbartha S. J. B.
ABSTRACT: The imbalance of the health workforce between rural and urban has the most severe impact in low-income countries (LICs). Lack of professional development opportunities, such as Continuing Medical Education (CME), is one of the key elements in this disparity. This research first presents a revised Citizen-centric Capacity Development (CCD) framework that focuses on goaldriven ICT solution design and impact assessment. It then investigates how the CCD framework guides the design, development, and assessment of CMES (CME on a Stick), a low-cost, integrative platform for the delivery of CME content to rural health workers in LICs. The success of the CMES project highlights the significance of the CCD framework in creating design artifacts that are contextually relevant, broadly scalable, and technologically sustainable. The research contributes not only to the theoretical knowledge of linking ICT interventions and development goals, but also the practical knowledge of ICT-based human capacity building in LICs.